Mexico : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper is a wide-ranging survey of the conditions for, and obstacles to, the growth in Mexico. It frames the issue of Mexico's growth record, and presents the paper's prior assumptions and approach. It highlights the main observations and conclusions emerging from the survey of growth conditions in Mexico. It also presents an overview of remittances in Mexico, motivated by their recent increase and possible macroeconomic implications.